2013
DOI: 10.4049/jimmunol.1300052
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Hsp70–TLR4 Pathway in Lethal Oxidant Lung Injury

Abstract: Administering high levels of inspired oxygen, or hyperoxia, is commonly used as a life-sustaining measure in critically ill patients. However, prolonged exposures can exacerbate respiratory failure. Our previous study showed that toll-like receptor 4 (TLR4) confers protection against hyperoxia-induced lung injury and mortality. Hsp70 has potent cytoprotective properties and has been described as a TLR4 ligand in cell lines. We sought to elucidate the relationship between TLR4 and Hsp70 in hyperoxia-induced lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 63 publications
1
55
0
Order By: Relevance
“…Extracellular Hsp70 exert its cytoprotective effect in lung endothelium through toll-like receptor 4 (TLR4) [19]. However, we did not observe increased Hsp70 in the medium of PAECs exposed to hyperoxia (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Extracellular Hsp70 exert its cytoprotective effect in lung endothelium through toll-like receptor 4 (TLR4) [19]. However, we did not observe increased Hsp70 in the medium of PAECs exposed to hyperoxia (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…1A). We previously reported 72 h of continuous hyperoxia as a time point of maximal lung injury, which we used as a representative time point (7). NLRP3 −/− , Asc −/− and Caspase 1/11 −/− mice exhibited significantly decreased lung injury (as assessed by bronchoalveolar lavage cell counts, protein and LDH), decreased reactive oxygen species generation (H 2 O 2 release detected by Amplex red assay), decreased lung cell death (assessed by TUNEL) and decreased IL1β secretion compared to WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NLRP3 −/− /PINK1 −/− mice were generated by crossing NLRP3 −/− mice with PINK1 −/− mice for >10 generations. Mice bred and exposure to hyperoxic as described previously (7). All protocols were reviewed and approved by the Animal Care and Use Committee at Yale University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we speculated that induction of HSP70 plays a protective role in PI-IBS mice via inhibiting NF-κB activation, following with the lower inflammation. This hypothesis has been validated in a mouse model of lethal oxidant lung injury which indicated that HSP70 mediated NF-κB activation to protect against hyperoxiainduced lung injury and the protective property of HSP70 is TLR4 dependent (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 93%